Integrating Computational Thinking and Spirituality in Developing Students’ Critical Thinking: A Comparative Study of Indonesia and Malaysia - Samsul Susilawati; Triyo Supriyatno; Ahmad Fatah Yasin; Zaidatun Tasir; Rika Inggit Asmawati; Abdulloh Chakim; Abd. Rahman Ambo’ Dalle (Jurnal Ilmiah Peuradeun, 2026)
Global educational challenges demand the development of critical thinking through approaches that integrate cognitive and ethical dimensions. This study examines how computational thinking and spirituality contribute to the development of students’ critical thinking skills in Indonesia and Malaysia. Using a quantitative design, data were collected from university students in both countries and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis reveals that computational thinking plays a more influential role in shaping students’ critical thinking in Malaysia, reflecting the strong emphasis on analytical and digital reasoning in instructional practices. In contrast, spirituality makes a stronger contribution in the Indonesian context, underscoring the importance of moral and spiritual values in supporting reflective and ethical reasoning. These differences highlight the role of cultural and pedagogical contexts in shaping cognitive development. Ultimately, the study demonstrates that integrating computational thinking and spirituality provides a holistic framework for strengthening students’ critical thinking, offering relevant implications for curriculum design and educational policy in higher education.